Cooling Induced Surface Reconstruction during Synthesis of High‐Ni Layered Oxides. Issue 43 (14th October 2019) - Zhang, Ming‐Jian; Hu, Xiaobing; Li, Maofan; Duan, Yandong; Yang, Luyi; Yin, Chong; Ge, Mingyuan; Xiao, Xianghui; Lee, Wah‐Keat; Ko, Jun Young Peter; Amine, Khalil; Chen, Zonghai; et al.
Abstract: Transition metal layered oxides have been the dominant cathodes in lithium‐ion batteries, and among them, high‐Ni ones (LiNi x Mn y Co z O2 ; x ≥ 0.7) with greatly boosted capacity and reduced cost are of particular interest for large‐scale applications. The high Ni loading, on the other hand, raises the critical issues of surface instability and poor rate performance. The rational design of synthesis leading to layered LiNi0.7 Mn0.15 Co0.15 O2 with greatly enhanced rate capability is demonstrated, by implementing a quenching process alternative to the general slow cooling. In situ synchrotron X‐ray diffraction, coupled with surface analysis, is applied to studies of the synthesis process, revealing cooling‐induced surface reconstruction involving Li2 CO3 accumulation, formation of a Li‐deficient layer and Ni reduction at the particle surface. The reconstruction process occurs predominantly at high temperatures (above 350 °C) and is highly cooling‐rate dependent, implying that surface reconstruction can be suppressed through synthetic control, i.e., quenching to improve the surface stability and rate performance of the synthesized materials. These findings may provide guidance to rational synthesis of high‐Ni cathode materials. Abstract : High‐nickel (Ni) layered oxides are promising cathode candidates for high energy density Li‐ion batteries. However, as Ni loading increases, synthetic control of structure/stoichiometry, especially at the surface, becomes a challenge. This work, through in situ X‐ray study into the synthesis of LiNi0.7 Mn0.15 Co0.15 O2 coupled with surface analysis, reveals cooling‐induced surface reconstruction, thereby enabling rational design of the synthesis to improve the surface properties of the synthesized materials.